Low-cost three-dimensional gait analysis system for mice with an infrared depth sensor - Nakamura, Akihiro; Funaya, Hiroyuki; Uezono, Naohiro; Nakashima, Kinichi; Ishida, Yasumasa; Suzuki, Tomohiro; Wakana, Shigeharu; Shibata, Tomohiro (Neuroscience research, 2015)
•A three-dimensional gait analysis system for mice has been developed.•The system tracks footprints and paw-tips precisely in the depth sensor coordinates.•Subjects’ gaits are captured from beneath using a low-cost infrared depth sensor.•An infrared-pass filter covers the floor and prevents a subject from acrophobia.•Subjects are more active on opaque floors than transparent floors. Three-dimensional (3D) open-field gait analysis of mice is an essential procedure in genetic and nerve regeneration research. Existing gait analysis systems are generally expensive and may interfere with the natural behaviors of mice because of optical markers and transparent floors. In contrast, the proposed system captures the subjects shape from beneath using a low-cost infrared depth sensor (Microsoft Kinect) and an opaque infrared pass filter. This means that we can track footprints and 3D paw-tip positions without optical markers or a transparent floor, thereby preventing any behavioral changes. Our experimental results suggest with healthy mice that they are more active on opaque floors and spend more time in the center of the open-field, when compared with transparent floors. The proposed system detected footprints with a comparable performance to existing systems, and precisely tracked the 3D paw-tip positions in the depth image coordinates.